Visual-Spatial and Intrapersonal Intelligence in Learning of Rampak Kendang Art for Elementary School Students - Fery Setyaningrum; Heni Siswantari (Graduate School of Institut Seni Indonesia Yogyakarta, 2020)
ABSTRACT The art of rampak kendang in Patimuan Cilacap Regency is an art that has existed for a long time and is hereditary in the people of Cilacap. In learning the art of rampak kendang, two types of plural intelligence exist and have their character in the form of visual-spatial and intrapersonal intelligence. This study aims to describe how visual-spatial and intrapersonal intelligence can form through the learning art of rampak kendang in elementary school students in Patimuan Cilacap. This research method uses descriptive research with a qualitative approach. Methods of data collection using observation, interviews, and document studies to analyze content, this study uses data validity techniques in the form of source triangulation, with data analysis techniques for data reduction, data presentation, and concluding. This study's results in the form of the formation of visual-spatial and intrapersonal intelligence are influenced by internal, external, textual, and contextual factors. Visuals spatial are formed based on understanding art through the senses, primarily through the eyes in the form of colour and space, then transforming the learning the art of rampak kendang captured by the eye into another type of recording and becoming a musical work that appears. In contrast, intrapersonal intelligence is formed with the ability to understand oneself and act based on understanding, which includes strengths and limitations of self, moods, intentions, motivations, temperament and desires, self-discipline, and self-understanding and respect. This study concludes that visual-spatial intelligence is created in the form of creating space by making floor patterns, observing and recording the trainer and then can mimic the movements of kendang, and the use of dancers 'and musicians' face makeup, and costume selection for performances. Intrapersonal intelligence appears based on listening to and playing music among musicians to create strength in oneself, calm the mood, control oneself, and be motivated so that it becomes more disciplined and more self-respecting and the environment. Kecerdasan Visual Spasial dan Intrapersonal dalam Pembelajaran Seni Rampak Kendang bagi Siswa Sekolah Dasar ABSTRAK Seni rampak kendang di Patimuan Kabupaten Cilacap merupakan kesenian yang sudah lama ada dan turun temurun pada masyarakat Cilacap. Dalam pembelajaran seni rampak kendang ditemukan ada dua jenis kecerdasan jamak yang ada dan memiliki karakternya sendiri berupa kecerdasan visual spasial dan intrapersonal. Penelitian ini bertujuan untuk mendeskripsikan proses kecerdasan visual spasial dan intrapersonal dapat terbentuk melalui pembelajaran seni rampak kendang pada siswa sekolah dasar di Patimuan Cilacap. Metode penelitian ini menggunakan jenis penelitian deskriptif dengan pendekatan kualitatif. Metode pengumpulan data menggunakan observasi, wawancara dan studi dokumen untuk menganalisis konten, penelitian ini menggunakan teknik keabsahan data berupa triangulasi sumber, dengan teknik analisis datanya reduksi data, penyajian data serta penarikan kesimpulan. Hasil penelitian ini berupa proses terbentuknya kecerdasan visual spasial dan intrapersonal dipengaruhi oleh faktor internal, eksternal, tekstual dan kontekstual. Visual spasial terbentuk berdasarkan memahami seni melalui pancaindera khususnya melalui mata berupa warna dan ruang, selanjutnya mentransformasikan bentuk dari pembelajaran seni rampak kendang yang ditangkap mata ke dalam bentuk wujud lain berupa rekaman dan menjadi karya musik yang rampak. Sedangkan kecerdasan intrapersonal terbentuk dengan kemampuan memahami diri sendiri dan bertindak berdasarkan pemahaman yang meliputi kekuatan dan keterbatasan diri, suasana hati, maksud, motivasi, temperamen dan keinginan, disiplin diri serta memahami dan menghargai diri. Kesimpulan penelitian ini adalah kecerdasan visual spasial tercipta berupa menciptakan ruang dengan membuat pola lantai, mengamati dan merekam pelatih kemudian bisa menirukan gerakan kendang, dan penggunaan make-up wajah penari dan pemusik, serta pemilihan kostum untuk pertunjukan. Sedangkan kecerdasan intrapersonal muncul ada berdasarkan mendengarkan dan memainkan musik antar anggota pemusik sehingga membuat kekuatan pada diri, menenangkan suasana hati, dapat mengendalikan diri, termotivasi sehingga menjadi lebih disiplin dan lebih menghargai diri serta lingkungan.